Assessing the leadership competencies of directors of private healthcare facilities in the North Central Region using the gap model - Nguyen The Hung; Le Hoang Ba Huyen (Technium Social Sciences Journal, 2026)
This study assesses the leadership competencies of directors of private healthcare facilities in Vietnam’s North Central region during 2020–2025 by integrating GAP analysis with partial least squares structural equation modeling (PLS-SEM). Data were collected from a survey of 496 respondents across five provinces in the region, complemented by in-depth expert interviews. The findings indicate that all competency domains are perceived as highly important, yet actual performance remains limited—particularly in digital competence and leadership skills. GAP and Importance–Performance Analysis (IPA) identify digital competence as the top improvement priority, whereas leadership attributes constitute a relatively stable strength. PLS-SEM results confirm that all four competency domains positively affect overall leadership competence, with digital competence exerting the strongest influence. Based on these findings, the paper proposes context-sensitive directions for leadership competency development tailored to local conditions to enhance governance effectiveness and promote the sustainable development of the region’s private healthcare system